Antipodean fields: Working with Bourdieu. (June 2013) - Bennett, Tony; Frow, John; Hage, Ghassan; Noble, Greg
The papers collected in this special issue of the Journal of Sociology seek both to develop a sense of the cumulative impact of Bourdieu's work on Australasian ('antipodean') debates, and to get a sense of how these debates might raise questions regarding the portability of Bourdieu's categories. We discuss the distinctive disciplinary orientations of the uptake of Bourdieu's work both here and internationally, and propose some explanations of the ways in which the antipodean uptake has modified its focus and conceptual force. These have to do, first, with the salience of different and more fluid models of the structural variables of class, gender and ethnicity; second, with a questioning of the nation-state as the 'natural' border of cultural fields; and third, with the way Indigeneity, in both Australia and New Zealand, is seen to transform the 'mainstream' culture and thereby to challenge many of the conventional ways of thinking about such things as cultural artefacts, cultural markets, and the 'rules of art'.